Kubernetes Networking: Challenges and Advances in Container Communication - Princess Egbuna, Oluebube (Journal of Science & Technology, 2024)
The intricacies, developments, and potential paths of Kubernetes networking in containerized settings are examined in this review. This study's primary goals were to explore the difficulties in Kubernetes networking architecture, look at new security and network policy developments, and discover ways to improve performance and Scalability. A thorough literature review of academic journals, technical reports, and industry publications was carried out to synthesize existing information and develop trends. Key findings show that fixing security flaws in multi-tenant settings, defining network policies across clusters, and guaranteeing compatibility with legacy systems are all challenging tasks. Promising answers to these problems can be found in the integration of service mesh technologies and improved encryption protocols, which are examples of advancements in network policies. The significance of standardized best practices for network security, real-time threat detection tools, and robust disaster recovery procedures is highlighted by policy implications. The present study enhances comprehension of the dynamic terrain of Kubernetes networking by emphasizing prospects for augmenting dependability, expandability, and safety within container communication frameworks.
Keywords: Kubernetes; Networking; Container Communication; Challenges; Advances; Microservices; Service Mesh; Network Policies; Load Balancing; Scalability